The Vietnamese refugee crises : a study of Singapore’s approach from 1975 to 1980 - Goh, Hannah Si Min (2019)
The question of why the Southeast Asian perspective of and involvement in the Vietnamese refugee crises of 1975 and 1978 has become a silent forgotten history can perhaps be answered by looking at why the voice of Vietnamese refugees themselves have been sidelined over the years and how similar colonial ideologies have shaped the formation of existing narratives within Southeast Asian. From the reflections of the resettlement process to academic studies on the Vietnamese refugee crises of 1975 and 1978, this paper seeks to surface and analyse how the domino logic, gendered politics and race contributed to Singapore’s response to the Vietnamese refugee crises between 1975 and 1980. Acknowledging the constraints of language in primary sources and availability of Vietnamese sources, this paper focuses on Singapore as a case study so as to comprehensively analyse the impacts and interactions between the three tropes mentioned above, drawing connections, preliminarily, between the responses of Singapore and ASEAN.